UPAYA ISLAMISASI ILMU PENGETAHUAN DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Iswati Iswati (Universitas Muhammadiyah Metro, 2017)
The purpose of this paper is to examine how the real efforts of Islamization of science and its implications tehadap Islamic education, and to prove that the idea of Islamization of knowledge is one of the phenomena of contemporary thinking movement activists of the Islamic world in the Era of the 1970s until the early 1980s. Operationally this study apply the methods of data analysis. The use of descriptive data analysis methods intended to analyze the thoughts and ideas of Islamization of science and its implications for the foundations of Islamic education. The primary sources referenced in this research is the work of thought Ismail al-Faruqi related to the concept of Islamization of knowledge with other Muslim thinkers like Syed Muhammad Naquib Al-Attas as it is known that since the onslaught of the discourse of Islamization knowledge, it invites experts to discuss. Among Muslim scholars have argued the importance of science to believe that science is necessary for Islamize, considering science in their outlook had been poisoned ideology and values of Western philosophy that much against the teachings of Islam. Al-Faruqi and Al-Attas appeared in their midst as the two central figures that are persistent and critical devote his ideas in modern science Islamization program. In their minds, the reality of the education that develops today embraces two educational systems, namely the system of Islamic education and secular education system, within the framework of the Islamisation of knowledge of both education system should be integrated into a system that is holistic so create education system powerful both materially and spiritually. Keywords: Islamization, Science, Islamic Education